(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical and paraclinical features and to evaluate the early outcomes of total pancreatectomy at the Department of Oncology and Radiation Therapy, Viet Duc University Hospital. Methods: A retrospective descriptive study of 23 patients undergoing total pancreatectomy from May 2018 to August 2025. Results: Mean age was 55.78 ± 20.14 years; male/female ratio ≈ 1.1/1. Abdominal pain occurred in 91.3% and malnutrition in 69.57%. The two leading pathologies were intraductal papillary mucinous neoplasm (30.43%) and pancreatic ductal adenocarcinoma (26.09%). Mean operative time was 478 ± 128 minutes with mean blood loss of 200 ± 80 ml. The R0 resection rate was 91.3%. Severe complication and perioperative mortality rate was 4.35%; mean hospital stay was 13 ± 2.5 days. At follow-up, 15/22 patients (68.18%) were alive, with a mean follow-up of 27.73 months. Conclusions: Total pancreatectomy is a feasible and safe surgical approach, associated with a high rate of R0 resection and improved quality of life in selected patients.